2017 IEEE Aerospace Conference 2017
DOI: 10.1109/aero.2017.7943946
|View full text |Cite
|
Sign up to set email alerts
|

NASA's Kilopower reactor development and the path to higher power missions

Abstract: The development of NASA's Kilopower fission reactor is taking large strides toward flight development with several successful tests completed during its technology demonstration trials. The Kilopower reactors are designed to provide 1-10 kW of electrical power to a spacecraft or lander, which could be used for additional science instruments, the ability to power electric propulsion systems, or support human exploration on another planet. Power rich nuclear missions have been excluded from NASA mission proposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…The Kilopower space reactor concept was proposed by NASA and supported by the Department of Energy (DOE). It aims to generate 1 to 10 kW electrical power that can be used for space exploration, electric propulsion systems, or planet exploration . Kilopower is a small space reactor system that uses heat pipes to deliver thermal energy from a highly enriched uranium (HEU) core to the Stirling engines, to produce electricity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kilopower space reactor concept was proposed by NASA and supported by the Department of Energy (DOE). It aims to generate 1 to 10 kW electrical power that can be used for space exploration, electric propulsion systems, or planet exploration . Kilopower is a small space reactor system that uses heat pipes to deliver thermal energy from a highly enriched uranium (HEU) core to the Stirling engines, to produce electricity.…”
Section: Resultsmentioning
confidence: 99%
“…It aims to generate 1 to 10 kW electrical power that can be used for space exploration, electric propulsion systems, or planet exploration. 24 Kilopower is a small space reactor system that uses heat pipes to deliver thermal energy from a highly enriched uranium (HEU) core to the Stirling engines, to produce electricity. NUSTER-10 and Kilopower are two novel reactor technologies with similar electrical power outputs, high safety features, and a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
“…Most significantly, Kilopower has served as a pathfinder, demonstrating that with correct application of technologies, use of existing facilities, and lean management, nuclear fission programs can be both successful and affordable [63]. Kilopower was designed for notional lunar and Mars surface NASA missions with electrical loads such as landers, habitats, mobility and construction equipment, and science experiments, and total power requirements ranging up to only 10kWe [64]. Unfortunately, the Kilopower reactor, or even Kilopowerderived technologies, do not appear to be translatable into the industrial-level use-case of the lunar propellant plant.…”
Section: Nuclear Fission 48mentioning
confidence: 99%
“…Recent ground tests demonstrated a 1 kWe 'Kilopower' system is both simple and viable for future space missions. 2,3 Combining a fission power system, leveraged from the kilopower demonstration, with the NEXT ion propulsion system at 7 kWe enables orbiting very deep space objects including Kuiper Belt objects (KBOs). Given the ample power available when NEP is not operating it was found that both higher power active science instruments could be used as well as high data rate communications to return the data quickly (instead of months required by the power limited New Horizons S/C.…”
Section: Figure 1 Nep Kboo Spacecraft (S/c)mentioning
confidence: 99%
“…In 2018 the 1 kWe DC variant of the Kilopower design was successfully tested at a DOE site in Nevada. 3 This reactor was coupled to 8 Stirling convertors (2 convertors, 6 simulators) which convert the reactor generated heat to electrical power. It was assumed that 8 Stirling convertors (only 6 were required to operate and provide full power) would be integrated with the reactor and heat would be rejected via a heat pipe radiator.…”
Section: Power Assumptionsmentioning
confidence: 99%